Delivery practices and care experience during implementation of an adapted safe childbirth checklist and respectful care program in Chiapas, Mexico. Issue 1 (12th March 2019) - Molina, Rose L.; Villar, Jimena; Reyes, Andrea; Elliott, James; Begley, Mark; Johnson, Mike; Palazuelos, Lindsay; Montaño, Mariana; Flores, Hugo; Semrau, Katherine E.A.; Palazuelos, Daniel
Abstract: Objective: To evaluate changes in quality of care after implementing an adapted safe childbirth checklist (SCC) in Chiapas, Mexico. Methods: A convergent mixed‐methods study was conducted among 447 women in labor who attended a rural community hospital between September 1, 2016, and June 30, 2017. Logistic regression analysis was used to evaluate adherence to evidence‐based practices over time, adjusting for provider. Participants were surveyed about their perceptions of care after hospital discharge. A purposefully sampled subgroup also completed in‐depth interviews. Thematic analysis was performed to evaluate perceptions of care. Results: 384 (85.9%) women were attended by staff that used the adapted SCC during delivery. Of these, 221 and 28 completed the hospital discharge survey and in‐depth interview, respectively. Adherence with offering a birth companion (odds ratio [OR] 3.06, 95% CI 1.40–6.68), free choice of birth position (2.75, 1.21–6.26), and immediate skin‐to‐skin contact (4.53, 1.97–10.39) improved 6–8 months after implementation. Participants' perceived quality of care improved over time. Provider communication generated positive perceptions. Reprimanding women for arriving in early labor or complaining of pain generated negative perceptions. Conclusion: Use of the adapted SCC improved quality of care through increased adherence with essential and respectful delivery practices. Abstract : Implementation of an adapted safe childbirth checklist in Mexico was associated with improved quality of care through increased adherence with essential and respectful birth practices.